Optimization of Breast Milk Production Through The Application of Oxytocin Massage Based on LLLT - Wiwik Puspita Dewi; Nevia Zulfatunnisa; Izzatun Nida Ulhaq; Diah Rosita (Universitas Duta Bangsa Surakarta, 2026)
Breast milk (ASI) production in the early postpartum period often encounters difficulties, requiring effective non-pharmacological interventions. Oxytocin massage and Low Level Laser Therapy (LLLT) are believed to enhance oxytocin reflex and facilitate lactation. Objective: To evaluate the effectiveness of combined oxytocin massage and LLLT on breast milk production among postpartum mothers and to analyze influencing maternal characteristics. Methods: This study employed a pretest–posttest one group design with 40 postpartum mothers. Breast milk production was measured using the pumping method before and after intervention. Data were analyzed using descriptive statistics, paired t-test, and bivariate analysis based on age, parity, education, and delivery history. Results: Mean breast milk production increased significantly from 2.2 ml/day to 75.5 ml/day (p<0.001). Bivariate analysis showed no significant differences by age, parity, or education (p>0.05), but delivery history was significantly associated with milk production (p=0.04). Conclusion: The combination of oxytocin massage and LLLT is clinically effective in enhancing breast milk production among postpartum mothers. Delivery history influences lactation outcomes, suggesting that this intervention has potential to be integrated into midwifery practice to support exclusive breastfeeding and stunting prevention.